2015
DOI: 10.1002/adfm.201403377
|View full text |Cite
|
Sign up to set email alerts
|

In‐Plane Alignment in Organic Solar Cells to Probe the Morphological Dependence of Charge Recombination

Abstract: Bulk heterojunction (BHJ) organic solar cells are fabricated with the polymer semiconductor aligned in the plane of the film to probe charge recombination losses associated with aggregates characterized by varying degrees of local order. 100% uniaxial strain is applied on ductile poly(3‐hexylthiophene):phenyl‐C61‐butyric acid methyl ester (P3HT:PCBM) BHJ films and characterize the resulting morphology with ultraviolet‐visible absorption spectroscopy and grazing incidence X‐ray diffraction. It is found that the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 14 publications
(21 citation statements)
references
References 34 publications
0
21
0
Order By: Relevance
“…There may be other losses associated with increased charge recombination in the strain‐oriented device that may contribute to the lower responsivity that would require further analysis. However, previous analysis on strain‐oriented P3HT:PCBM devices showed that internal quantum efficiency only slightly reduced compared to control spun‐cast films, suggesting that the primary difference in EQE was due to absorption differences . Despite the reduced R (and EQE) in strain‐oriented films, the performance metrics still compare favorably to other high‐performing all‐polymer photodetector demonstrations.…”
Section: Resultsmentioning
confidence: 84%
“…There may be other losses associated with increased charge recombination in the strain‐oriented device that may contribute to the lower responsivity that would require further analysis. However, previous analysis on strain‐oriented P3HT:PCBM devices showed that internal quantum efficiency only slightly reduced compared to control spun‐cast films, suggesting that the primary difference in EQE was due to absorption differences . Despite the reduced R (and EQE) in strain‐oriented films, the performance metrics still compare favorably to other high‐performing all‐polymer photodetector demonstrations.…”
Section: Resultsmentioning
confidence: 84%
“…From Eq. (24), it is also notable that there is a small (average 3%) S 3 response in the second and third OPVs. This is due to the stress birefringence contained within the strained polymer film.…”
Section: Model Validationmentioning
confidence: 89%
“…A detailed analysis of the polarized OPV cell performance has shown that the internal quantum efficiency of the device remains similar to an unstrained device and is independent of the incident polarization state [24]. Thus the strained devices have a similar efficiency of collecting photogenerated carriers as an archetypal processed counterpart and the anisotropic performance is attributed primarily to the difference in light absorption in the cell.…”
Section: Detector Considerations and Fabricationmentioning
confidence: 94%
“…Large‐area alignment can be achieved using casting techniques such as directional solidification, solution shearing, and microchannel confinement, yielding anisotropic, and in some cases substantially improved, carrier mobilities . Mechanical post‐processing techniques such as stamping, rubbing, and straining have also been shown to induce polymer chains to adopt highly aligned configurations . Molecular design of polymers exhibiting liquid crystalline behavior has also been used to supplement the effectiveness of alignment techniques …”
Section: Introductionmentioning
confidence: 99%
“…10,[15][16][17] Mechanical post-processing techniques such as stamping, rubbing, and straining have also been shown to induce polymer chains to adopt highly aligned configurations. [18][19][20][21][22] Molecular design of polymers exhibiting liquid crystalline behavior has also been used to supplement the effectiveness of alignment techniques. 16,23 The aforementioned macroscopic alignment techniques focus on in-plane alignment, but for some applications, such as organic photovoltaics, transport along the out-of-plane or "vertical" direction is of greater interest.…”
mentioning
confidence: 99%